2016
DOI: 10.1159/000454778
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Lipoprotein-Associated Phospholipase A2 in Monocyte Subsets: Impact of Uremia and Atherosclerosis

Abstract: Background: Monocytic products, such as lipoprotein-associated phospholipase A2 (Lp-PLA2), may participate in the development of atherosclerosis. Heterogeneity of monocytes is widely acknowledged. Classical, intermediate, and non-classical subsets can be discerned. Recently, an inflammatory, pro-atherogenic monocyte population could be identified in hemodialysis patients. In this study, we investigated the expression of Lp-PLA2 on leucocytes and different monocyte subpopulations and their possible role in urem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…At present, it has been considered that (Alkuraishy et al, ; Yang et al, ) some kinds of Lp‐PLA2 that can bind with high density lipoprotein (HDL) can hydrolyze oxidized phospholipids in blood, reduce the accumulation of inflammatory mediators in phagocytes, and inhibit foam cell formation, thereby exerting anti‐inflammatory and anti‐atherosclerotic effects. In the process of the hydrolysis of oxidized low‐density lipoprotein (ox‐LDL), sLp‐PLA2 produces oxidized free fatty acids (ox‐FFA) and lysolecithin (lyso‐PC) (Bonnefont‐Rousselot, ; Ulrich et al, ). These two potent inflammatory substances damage endothelial cells and induce the expression of adhesion factors through oxidative stress and promote monocytes to aggregate into the lumen to form macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…At present, it has been considered that (Alkuraishy et al, ; Yang et al, ) some kinds of Lp‐PLA2 that can bind with high density lipoprotein (HDL) can hydrolyze oxidized phospholipids in blood, reduce the accumulation of inflammatory mediators in phagocytes, and inhibit foam cell formation, thereby exerting anti‐inflammatory and anti‐atherosclerotic effects. In the process of the hydrolysis of oxidized low‐density lipoprotein (ox‐LDL), sLp‐PLA2 produces oxidized free fatty acids (ox‐FFA) and lysolecithin (lyso‐PC) (Bonnefont‐Rousselot, ; Ulrich et al, ). These two potent inflammatory substances damage endothelial cells and induce the expression of adhesion factors through oxidative stress and promote monocytes to aggregate into the lumen to form macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, relative to people without diabetes, there is a fourfold increase in intracellular Lp-PLA2 levels in adipose tissue from individuals with type 2 diabetes; this may, in part, explain the systemic changes in Lp-PLA2 plasma levels in type 2 diabetic individuals. It should also be noted that other cell types secrete Lp-PLA2, such as monocytes, macrophages, T lymphocytes and mast cells, providing an additional source of circulating Lp-PLA2 in type 2 diabetes [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with Caslake et al, [27] who demonstrated that LP-LPA2 levels were higher in 94 patients with CAD than in 54 controls. The connection remained even after controlling for LDL and HDL-cholesterol, smoking, and systolic blood pressure [28].…”
Section: Discussionmentioning
confidence: 88%